Linguistic features of English terminologies on Ear, Nose, Throat and their Vietnamese equivalents / Nguyen Thu Hien; Supervisor: Assoc.Prof.Dr. Phan Van Que - Nguyen, Thu Hien
This study was carried out to investigate English terminologies on Ear, Nose, Throat in the textbook Pocket Tutor Paediatric Clinical Examination by Rossa Brugha, Matko Marlais and Ed Abrahamson and their Vietnamese equivalents. The analysis was based on 90 terminologies on ear, nose, throat collected in chapter 13 of the textbook. The Vietnamese version was translated by a group of doctors and students at Hai Phong University of Medicine and Pharmacy. The collected terminologies were divided and analyzed in terms of morphological, lexical, and syntactic features. Two research approaches of quantitative and qualitative are employed in this study. After the data are collected and processed, the features of terminologies in terms of morphological, lexical, and syntactic features are quantitatively described by means of statistic tables and figures to show their distribution and percentage. The results are then discussed and interpreted qualitatively to determine some notable features. Next, contrastive analysis is used to discover the similarity and difference between the English terms and their Vietnamese translation. This study looked at how some of the most commonly used ENT terms are constructed and how this may facilitate the building of a wider medical vocabulary for medical students. In addition, this study also examined the specific features of medical English in an effort to clearly delineate medical English for curricular and instructional purposes. Specifically, the linguistic features that characterize medical English are explored. This exploration relies on corpus linguistic data collected from this study in order to examine specific morphological, lexical and syntactic features of medical English. The findings suggest that medical English can be characterized as a legitimate register of English with the linguistic features of proportional specialized medical vocabulary.